Faktor-Faktor Yang Mempengaruhi Opini Audit Going Concern (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Rahmadona, Suci; Sukartini; Djefris, Dedy (Akuntansi dan Manajemen, 2019)
Going concern audit opinion is an opinion issued by the auditor to ascertain whether the company can maintain its survival. This research was conducted to examine the factors that influence the going concern audit opinion. These factors are, company size, company growth, solvency and previous year's audit opinion. The sample in this study are mining companies listed on the Indonesia Stock Exchange during the 2015-2017 period. The sample selection is done by purposive sampling technique, namely the selection of samples based on certain criteria. So that the total sample of this study was 60 samples. Data analysis used is logistic regression analysis using SPSS version 20. The results of this study are company size, company growth and solvency does not affect the going concern audit opinion. Whereas, the previous year's audit opinion affects the going-concern audit opinion.